Strain measurement at temperatures up to 800°C using regenerated gratings produced in the highGe-doped and B/Ge co-doped fibers - Zhang, P.; Yang, H.Z.; Wang, Y.; Liu, H.; Lim, Kok Sing; Gunawardena, D.S.; Ahmad, Harith (Optical Society of America, 2017)
In this work, we have proposed a sensor for strain measurement in high-temperature environments up to 800°C by employing two regenerated fiber Bragg gratings. Two seed gratings (SGs) are inscribed in high Ge-doped and B/Ge-codoped fibers, respectively, which possess different temperature sensitivities. To achieve two gratings with different strain sensitivities, one of the gratings is chemically etched to reduce the fiber diameter for strain sensitivity enhancement. A thermal annealing process is carried out to activate the grating regeneration in the SGs. The temperature and strain calibration experiments indicate that the proposed structure has uncertainty values of 23.42 με and 5.83°C over the ranges of 0–1000 με and 20°C–800°C, respectively.